Biofuels from digested sewage sludge pyrolytic biofuel production and catalytic upgrading studies - Arazo, Renato O.; De Luna, Mark Daniel G.; Capareda, Sergio C. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The search for liquid biofuels to augment petroleum-based fuel has led to the increased interest in finding non-traditional, non-food biomass as sources for biofuels. In this work, the applicability of using digested sewage sludge as feedstock for producing second generation diesel range liquid biofuel via a two-stage fast pyrolysis/catalytic upgrading processes is investigated. The process conditions such as reaction temperature, sludge particle size, and vapor residence time for fast pyrolysis were optimized using response surface methodology with respect to yield, heating value and moisture content of the fast pyrolysis oil. Catalytic upgrading over a Ni/HZSM-5 catalyst was then conducted by varying the reaction temperature, ethanol to bio-oil mass ratio, and reaction time. Results of the study demonstrated that domestic sewage sludge largely made up of fecal waste makes as good feedstock for producing bio-oil with high heating value of 36.43 MJ/kg, nearly comparable to commercial heavy fuel oil of 40 MJ/kg. FTIR and GC-MS analyses of the bio-oil showed that its major fractions (42.17%) were gasoline range compounds (alkanes, alkenes, and aromatics) with considerable proportion of oxygenated compounds such as ketones (11.72%) and phenols (15.28%), and nitrogenated compounds (18 .75%). Catalytic upgrading with ethanol co-feed dramatically reduced the percentage of the undesirable oxygenated and nitrogenated compounds resulting to a highly-desirable product with high heating value of 39.97 Ml/kg and composed largely of esters (48.59%), aromatics (9.38%), alkanes (10.12%) and alkenes (5 .08%). This study demonstrated that the combined fast pyrolysis/catalytic upgrading processes are capable of producing excellent biofuels from digested sewage sludge, with huge implication for biofuels production.
Thesis (Ph. D. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Biomass energy; Sewage sludge fuel; Pyrolsis